Self emulsifying systems: A review (Asian Journal of Pharmaceutics (AJP), 2015)
As a consequence of modern drug discovery techniques, there has been a steady increase in the number of newÂ pharmacologically active lipophilic compounds that are poorly water soluble. It is a great challenge for pharmaceuticalÂ scientists to convert those molecules into orally administered formulations with sufficient bioavailability. Among theÂ approaches to improve the oral bioavailability of these molecules, the use of self-emulsified drug delivery systems (SEDDS)Â has been shown to be reasonably successful in improving the oral bioavailability of poorly water-soluble and lipophilic drugs.Â SEDDS, which are isotropic mixtures of oils, surfactants, solvents and coâ€solvents/surfactants, can be used for the design ofÂ formulations in order to improve the oral absorption of highly lipophilic drug compounds. It can be orally administered inÂ soft or hard gelatin capsules.These systems form fine emulsions (or microâ€emulsions) in the gastrointestinal tract (GIT) withÂ mild agitation provided by gastric mobility. Many parameters like surfactant concentration, oil/surfactant ratio, polarity ofÂ the emulsion, droplet size and charge play a critical role in oral absorption of drug from SEEDS. This formulation enhancesbioavailability due to increase in the solubility of the drug and minimizes gastric irritation.Key words: Bioavailability, emulsions, isotropic, selfâ€emulsifying drug delivery systems